Scaling Up Transformational Change: Facing Up to Global Megatrends and Their Environmental Impacts - Kashmanian, Richard M. (Environmental Management and Sustainable Development, 2022)
In light of significant environmental impacts from past and projected global population, demographic, and environmental megatrends, this article makes the case why incremental change is insufficient to alter these environmental trends and that there is thereby a growing commitment to transformational change. In addition, there is increasing recognition of the urgent need for scaling up transformational change across entire sectors and systems to achieve systemwide changes that will be needed to reverse these negative environmental trends, help pull the Earth system within proposed planetary boundaries that have been exceeded, and achieve long-term global sustainability goals. This article makes the case for the need for transformational change and scaling up transformational change to achieve system-wide change. Given the magnitude of what it will take to transform systems and the important role of the private sector due to its more direct environmental impacts, it will be important for companies to be leaders in these efforts to scale up transformational change, and their collaboration with key stakeholders will be vital. This article identifies examples of leading efforts by several companies and proposes that it will be important for many companies to combine such or similar efforts to not only protect habitats and species but to also restore critical habitats. There is a call for the private sector and also other stakeholder groups, such as governments, investors, civil society, and consumers, to jointly collaborate and collectively respond to these challenges and lead.